2021
DOI: 10.1186/s11658-021-00255-y
|View full text |Cite
|
Sign up to set email alerts
|

Triazoloacridone C-1305 impairs XBP1 splicing by acting as a potential IRE1α endoribonuclease inhibitor

Abstract: Inositol requiring enzyme 1 alpha (IRE1α) is one of three signaling sensors in the unfolding protein response (UPR) that alleviates endoplasmic reticulum (ER) stress in cells and functions to promote cell survival. During conditions of irrevocable stress, proapoptotic gene expression is induced to promote cell death. One of the three signaling stressors, IRE1α is an serine/threonine-protein kinase/endoribonuclease (RNase) that promotes nonconventional splicing of XBP1 mRNA that is translated to spliced XBP1 (X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…In the current study, we observed that genetic targeting of XBP1 is significantly more deleterious to cells with hyperactive AKT ( Figure 4 B). XBP1 production is potentially targetable through the chemical inhibition of IRE1α, and numerous compounds with such activity have been described [ 54 , 55 , 56 , 57 , 58 , 59 ]. However, IRE1α has been reported to carry out other important functions, such as housekeeping control of mitochondrial calcium uptake [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we observed that genetic targeting of XBP1 is significantly more deleterious to cells with hyperactive AKT ( Figure 4 B). XBP1 production is potentially targetable through the chemical inhibition of IRE1α, and numerous compounds with such activity have been described [ 54 , 55 , 56 , 57 , 58 , 59 ]. However, IRE1α has been reported to carry out other important functions, such as housekeeping control of mitochondrial calcium uptake [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…CTRL cells were treated with vehicle CTRL, DMSO (< 0.5% v/v; Sigma, D2650). Furthermore, to verify IRE1 activity, cells treated were 20 µM 4µ8C (an IRE1 inhibitor, Sigma-Aldrich, SML0949) dissolved in DMSO (Sigma-Aldrich, St. Louis, MI, USA) [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Proper ER functionality is essential for cells; however, various conditions can interfere with its operation, leading to a build up of proteins, referred to as ER stress [ 35 ]. Unfolded protein response (UPR) is caused by the build up of misfolded proteins in the ER, which is the classical signaling pathway for ER stress [ 36 , 37 ]. UPR might be activated by specific conditions including dithiothreitol (DTT), tunicamycin (Tm), and low concentrations of inositol [ 38 ].…”
Section: Functions Of Fitm Proteinsmentioning
confidence: 99%